Development of E-modules as a Learning Resource for Prayer Practice - Gugun Ismawan; Imam Tabroni; Goldwag Megan; Bouyea Jonathan (Journal Emerging Technologies in Education, 2023)
Background. This research is motivated by the rapid development of increasingly sophisticated technology in the era of globalization, so educators are also required to have IT skills that can support learning and make teaching materials more creative and innovative. Purpose. But at SMPN 1 Bungursari in learning Islamic Religious Education still does not utilize the sophistication of technology that is available. This research is a development research consisting of three stages, namely. Method. the definition stage (define), the design stage (design) and the development stage (develop). This research instrument uses validation sheets and questionnaires. The module was validated by three validators, namely one media lecturer, one Islamic religious education lecturer, and one Islamic religious education teacher. At the stage of practicality and effectiveness of e-modules as a learning resource for prayer practice, it was tested on 26 students of class VII SMPN 1 Bungursari. Results. Based on the results of data analysis that has been done, it can be concluded as follows: (1) The results of validation of e-modules as a learning resource for prayer practice material developed for class VII SMPN 1 Bungursari are valid with a percentage of 85.3%. Conclusion. The results of the trial of the practicality of the e-module as a learning resource for prayer practice material developed showed the results of teacher practicality of 90.2% and student practicality of 85.4% with a very practical category that can be used in the learning process.